Effects of short-term bee bread supplementation on peak torque and average power of the lower limb - Chee Ping Fadzel Wong (UniSE Press, 2024)
Bee products are the common type of ergogenic aid to enhance exercise performance in athletes. Athletes consume bee products such as bee bread to make sure they have adequate nutrition and maximize their energy storage. To date, research on ergogenic effects of short-term bee bread supplementation on peak torque and average power of the lower limb in male athletes is still limited. Therefore, this study investigates the impact of short-term bee bread supplementation on peak torque and average power in the lower limbs of male athletes. Twelve athletes were selected and recruited in this randomized cross-over study. Subjects consumed either bee product or placebo for 8 weeks prior to the experimental trial. The Isokinetic dynamometer (Multi Joint System 3 Pro: Biodex Medical System, USA) was used to measure subjects’ peak torque and average power of the isokinetic lower limb. Statistical analyses were performed using ANOVA with repeated measures. This present study found that isokinetic right knee extension and flexion of peak torque and average power at 180o .s-1 was significantly higher in post-test compared to pre-test in the bee bread trial (p<0.05). The study discovered that bee bread supplementation had beneficial effects on the lower limb in male athletes.